(untitled) (KULT_online, 2012)
The historian Olaf Hartung looks at the history of the German museum landscape in a tight overview of events from the late 18th century to the time of the Weimar Republic. He describes seven types of museums: art, culture-historical, applied arts and design, ethnographical, technical, natural science, and the local or regional museum. The design of the book allows one to consult it like a manual and provides concentrated knowledge about the beginnings of modern museums.